HUBUNGAN SCREEN TIME, KEBIASAAN MAKAN JUNK FOOD, AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA REMAJA DI MAN 14 JAKARTA TIMUR - Rezeki, Sri; Suryaalamsah, Inne Indraaryani (Universitas Negeri Medan, 2023)
Based on the results of the 2018 Basic Health Research, the prevalence of adolescents aged 15 years who have central obesity is 31.0%. Obesity occurs due to the income of certain population groups, and eating habits that have begun to shift to disproportionate foods such as low carbohydrate, high fat and low fiber foods, as well as less physical activity caused by busyness and screen time. The aim of this study was to analyze the relationship between screen time, junk food eating habits and physical activity with obesity in teenagers at MAN 14 East Jakarta. The research was conducted in May 2023 at Madrasah Aliyah Negeri 14 East Jakarta with a sample size of 57 respondents aged 16 - 17 years. The sampling technique uses simple random sampling. This research uses quantitative research methods with a cross sectional design. Data were collected using a screen time questionnaire, for junk food eating habits using the FFQ and physical activity using the physical activity level (PAL), then the data was analyzed using the chisquare test. The results of the study showed that there was a relationship between screen time (p= 0.000), junk food eating habits (p= 0.000), and physical activity (p= 0.032) with the incidence of obesity in adolescents. It is hoped that MAN 14 East Jakarta students can increase physical activity and reduce screen time habits and consumption of junk foodKeywords physical activity, Junk food, Screen Time, Obesity